Professional Identity Development Through Service Learning: A Qualitative Study of First-Year Medical Students Volunteering at a Medical Specialty Camp. (November 2015) - Beck, Jimmy; Chretien, Katherine; Kind, Terry
Objective . To describe the experience of medical students volunteering at a camp for children with a variety of medical conditions. Methods . Rising second-year medical students who had served as counselors for 1 week at a medical specialty camp were invited to participate. We conducted a 2-part qualitative study using on-site focus groups and follow-up individual interviews. Results . Nine medical students participated. Students described their experience as motivating and career reinforcing. It helped them "move beyond the textbook" and deepened their commitment to serving future patients with compassion. One theme that emerged was the idea that their camp experience fostered the development of their professional identities. Conclusions . A 1-week, immersive community service experience at a medical specialty camp played a role in influencing the early formative professional identities of rising second-year medical students. Medical schools could use camps as a promising community service-learning experiences to foster professional identity.